EDUKASI MP-ASI DI DESA PERCUT KABUPATEN DELI SERDANG - Mayasari Rahmadhani (Universitas Islam Sumatear Utara, 2023)
ASI is the best intake because it has the amount of nutrients needed to protect a baby from various diseases. As the baby grows, so does the need for nourishment, so at the age of 6 months, the baby begins to be fed maternal feeding. MP-ASI maybe given from 6 months to 24 months. Mothers with good knowledge about MP-ASI will bring children to grow an develop well. A mother’s knowledge of the can MP-ASI include understanding, the benefit, the role, the manner of giving, ang the risk of giving. Providing good companion food ASI would have a good effect on the baby’s health and instead. The study used a type of experimental with the design of one group pre test – post test. The population in this study is all the mothers who have children aged 0 to 24 months in the village Percut district’s Deli Serdang. The technique used in determining a sample is to use the saturated sample in which all the population counts will be samples. And the number of samples is 23 people. With education comes increased knowledge from 13,0% increased to 60,9%.